Spondylodiscitis complicating infective endocarditis. Issue 24 (28th May 2020) - Carbone, Andreina; Lieu, Audrey; Mouhat, Basile; Santelli, Francesco; Philip, Mary; Bohbot, Yohann; Tessonnier, Laetitia; Peugnet, Fanny; D'Andrea, Antonello; Cammilleri, Serge; Delpierre, Quentin; Gouriet, Frédérique; et al.
Abstract : Objective: The primary objective was to assess the characteristics and prognosis of pyogenic spondylodiscitis (PS) in patients with infective endocarditis (IE). The secondary objectives were to assess the factors associated with occurrence of PS. Methods: Prospective case–control bi-centre study of 1755 patients with definite IE with (n=150) or without (n=1605) PS. Clinical, microbiological and prognostic variables were recorded. Results: Patients with PS were older (mean age 69.7±18 vs 66.2±14; p=0.004) and had more arterial hypertension (48% vs 34.5%; p<0.001) and autoimmune disease (5% vs 2%; p=0.03) than patients without PS. The lumbar vertebrae were the most frequently involved (84 patients, 66%), especially L4–L5. Neurological symptoms were observed in 59% of patients. Enterococci and Streptococcus gallolyticus were more frequent (24% vs 12% and 24% vs 11%; p<0001, respectively) in the PS group. The diagnosis of PS was based on contrast-enhanced MRI in 92 patients, bone CT in 88 patients and 18 F-FDG PET/CT in 56 patients. In-hospital (16% vs 13.5%, p=0.38) and 1-year (21% vs 22%, p=0.82) mortalities did not differ between patients with or without PS. Conclusions: PS is a frequent complication of IE (8.5% of IE), is observed in older hypertensive patients with enterococcal or S. gallolyticus IE, and has a similar prognosis than other forms of IE. Since PS is associated with specific management, multimodality imaging including MRI, CT and PET/CT should be used for early diagnosis of this complication of endocarditis.